Effect of Customer Value and Trust on Patient Revisit Intention: Satisfaction as Mediator - Salsabila Az Zahra; Naili Farida; Septo Pawelas Arso (State Islamic University of Sunan Ampel, 2023)
Customer value is an important marketing strategy aspect that refers to the evaluation of products that meet value and satisfaction. Hospital has intangible characteristics of services so trust is needed. Hospitals need to instill credibility to the extent that customers believe that they can provide service products that satisfy customer needs. This study aims to determine the effect of customer value and hospital trust on repeat visits at Bekasi Public Hospital. The type of research is a quantitative observational cross-sectional using random sampling. PLS-SEM was used to evaluate the data of 125 respondents who were patients outpatient. The results of this study indicate that customer value has an effect on satisfaction, trust has an effect on satisfaction, customer value and satisfaction have an effect on the revisit intention, and trust has no effect on the revisit intention. Customer value can affecttsatisfaction and revisit intention and trust affect patient satisfaction, but trust does not directly affect intention to revisit. Satisfaction can affect the patient's revisit intention.